ANALISIS PREDIKSI PENJUALAN DENGAN METODE REGRESI LINEAR DI PT. EAGLE INDUSTRY INDONESIA - Miftahuljannah; Aswan Supriyadi Sunge; Ahmad Turmudi Zy (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
When making the crucial decision to determine the outcome of a case. The goal of this study is to evaluate the potential for product sales. With the help of data mining, this study evaluates the potential for litigation by using data from several sources, including product, plan, and current data. The current study makes use of the linear regressive algorithm and the rapidminer data processing tool. The dataset that was used for this study was divided into two parts: one half of the data for teaching and one half of the data for research. Using a linear regression algorithm, the results show that the variables or attributes used in the current analysis (produk, actual and plan) did not significantly affect the results. Squared Error is 1313427569.481 +/- 5882150128.134, and Root Mean Squared Error is 36241.241 +/- 0.000. This indicates that the squared Error generates a higher number than the Root Mean Squared Error.